Democracy and the Peoples’ Tribunal in Joko Widodo’s Era: A Study Based on Responsive Law Theory - Nawaz Syarif; Muhammad Torieq Abdillah; Yamani Naufal (DiH: Jurnal Ilmu Hukum, 2026)
This research addresses the decline of democracy and rule of law in Indonesia under President Joko Widodo, characterized by political dynasties, judicial weakening, and laws favoring political power.itical power. These conditions led to the emergence of the Peoples’ Tribunal or Extraordinary Peoples’ Court as a public effort to demand substantive justice. The purpose of this study is to analyze the legitimacy of the Peoples’ Tribunal within Indonesia’s rule of law framework through Responsive Law Theory. This study employs normative legal research using statutory, conceptual, and case study approaches. Data were collected from relevant regulations, court decisions, and scholarly literature, then analyzed using content analysis. The findings reveal that although the Peoples’ Tribunal has no binding legal force, it holds moral and social legitimacy as a corrective mechanism against the failures of formal legal institutions. From the perspective of responsive law, the phenomenon reflects society’s demand for a more adaptive, participatory, and reflective legal system, while also serving as a critique of Indonesia's increasingly formalistic and elitist legal order.